Capping risk adjustment? - Patrick Eugster; Michèle Sennhauser; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2009)
When premiums are community-rated, risk adjustment (RA) serves to mitigate competitive insurers'; incentive to select favorable risks. However, unless fully prospective, it also undermines their incentives for efficiency. By capping its volume, one may try to counteract this tendency, exposing insurers to some financial risk. This in term runs counter the quest to refine the RA formula, which would increase RA volume. Specifically, the adjuster, Hospitalization or living in a nursing home during the previous year will be added in Switzerland starting 2012. This paper investigates how to minimize the opportunity cost of capping RA in terms of increased incentives for risk selection.
Keywords: 330; Private Krankenversicherung; Risikomodell; Risikoprämie; Adverse Selektion; Schweiz